Topography of the subducting basement throughout the entire Nankai Trough - Kazuya Shiraishi; Yasuyuki Nakamura; Ryuta Arai; Tetsuo No; Yuka Kaiho; Ryo Miura; Ayako Nakanishi; Seiichi Miura; Gou Fujie; Shuichi Kodaira (Scientific Reports)
Abstract The heterogeneous distributions of large and slow earthquakes in subduction zones are caused by multiple uncertain conditions in the source regions, and the basement topography is considered one of the major controlling factors. We revealed the topography of the subducting basement along the entire Nankai Trough on the basis of seismic reflection profiles compiled from 1997 to 2024. We interpreted the reflection profiles in the time domain to ensure consistency among multiple-generation datasets. The new surface model captured the detailed topography on a scale of several kilometers, over 730 km long and 150 km wide, and down to depths of 15–20 km. The basement topography is characterized by past tectonic activity and is divided into three domains, which affect the present heterogeneity in geological structures and physical properties along the Nankai Trough. While the three domains correspond to megathrust seismogenic zones along the Nankai Trough, the lack of correspondence between the significant topographic relief and the slow earthquake distribution in some areas suggests the need for additional factors controlling spatiotemporal variations in seismicity.